Analisis Sikap Dan Kepuasan Konsumen Terhadap Kopi Liberika (Studi Kasus Pada One Refinery Coffee) Kota Pekanbaru - Afri, Reza Azalita; Maharani, Evy; Eliza, Eliza (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Coffee consumption Indonesia increase in 2020-2021 with a consumption level of 5,000 kg. It is estimated that Coffee consumption in Indonesia continues to increase in 2020-2021 with a consumption level of 5,000 kg. It is estimated that domestic coffee consumption from 2020-2024 will increase by an average of 3.07% per year. This increase in coffee consumption makes the prospect of coffee agribusiness in Indonesia a good business opportunity to develop for every producer. This has encouraged the emergence of various coffee shops in big cities such as the city of Pekanbaru. The development of coffee shops in Pekanbaru City is accompanied by an increase in lifestyle in various groups of society, both young and old, which is supported by affordable prices and practicality of presentation. Liberica coffee is a type of coffee that can be created into various types of drinks. One Refinery Coffee is a coffee shop in the city of Pekanbaru that sells and processes Liberica coffee beans into coffee powder and ready-to-drink drinks. This research aims to analyze the level of performance and importance of marketing mix attributes, as well as analyzing the level of consumer satisfaction with the marketing mix attributes of Liberika One Refinery Coffee in the city of Pekanbaru. Sampling used the Accidental Sampling method. Data was analyzed using Importance Performance Analysis and Customer Satisfaction Index. The research results show that the level of performance and importance of the marketing mix variables are product, price, place and promotion, respectively. Based on the results of the Cartesian diagram analysis, the attributes that are priority improvements are coffee taste, coffee aroma, coffee menu variations, decorative toppings on coffee and parking space because according to consumers these attributes are important but have low performance. Overall, consumers are satisfied with the performance of the marketing mix attributes.